2015
DOI: 10.1111/1462-2920.13097
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐borne reservoirs of antibiotic‐resistant bacteria are established following therapeutic treatment of dairy calves

Abstract: SummaryWe determined if antibiotics residues that are excreted from treated animals can contribute to persistence of resistant bacteria in agricultural environments. Administration of ceftiofur, a third-generation cephalosporin, resulted in a ∼ 3 log increase in ceftiofur-resistant Escherichia coli found in the faeces and pen soils by day 10 (P = 0.005). This resistant population quickly subsided in faeces, but was sustained in the pen soil (∼ 4.5 log bacteria g −1 ) throughout the trial (1 month). Florfenicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 34 publications
(40 reference statements)
2
41
0
Order By: Relevance
“…We postulate that the temporal increase in E. coli concentrations in occupied pens was due to the deposited E. coli populations themselves, increased nutrients from the deposited manure, or a combination of these factors. These findings and postulations are consistent with recent studies that found antimicrobial-resistant bacteria and antimicrobial resistance genes increased in soils from pens holding cattle that had not received antibiotics and soils fertilized with manure from dairy cattle that had not received antibiotics (30,33).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…We postulate that the temporal increase in E. coli concentrations in occupied pens was due to the deposited E. coli populations themselves, increased nutrients from the deposited manure, or a combination of these factors. These findings and postulations are consistent with recent studies that found antimicrobial-resistant bacteria and antimicrobial resistance genes increased in soils from pens holding cattle that had not received antibiotics and soils fertilized with manure from dairy cattle that had not received antibiotics (30,33).…”
supporting
confidence: 91%
“…Concerns also have been raised that in-feed CTC could increase the occurrence of antimicrobial resistance in pen surface soil, possibly reinoculating cattle with resistant bacteria or increasing the occurrence of antimicrobial resistance in manure, which may impact crops or the environment (29)(30)(31)(32). To our knowledge, the impact of in-feed CTC on beef cattle feedlot pen surface generic, TET r , and 3GC r E. coli occurrences has not been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On H farms, a high within-sample prevalence of QREC was observed in the calf feed and water troughs and in milk bucket samples. The MLVA was not used to test movement within farms; however, we can assume, based on these results, that the bacterial flora surrounding the calves may play an essential role in the presence of bacteria in their gastrointestinal (GI) tract, which was also observed in a recent study by Liu et al (13). A high prevalence of QREC in feed and water troughs may ease the fecal-oral circulation of QREC, which was also suggested by Yamamoto et al (14) to be important for the on-farm dissemination of multidrug-resistant E. coli.…”
Section: Discussionmentioning
confidence: 96%
“…Antibiotics are therefore used as growth promoters and prophylactics, which has led to an explosive increase in the prevalence of antibiotic-resistant bacteria, threatening livestock and human health [71,72]. Although the use of antibiotics to promote growth is restricted in the EU [73], even the therapeutic use of antibiotics has resulted in the spread of antibiotic-resistant bacteria among livestock [74,75].…”
Section: Antibiotic Usementioning
confidence: 99%